유방암에서 Cyclophosphamide , Thiotepa , Carboplatin ( CTCb ) 고용량 복합항암화학요법 후 자가말초혈액 조혈모세포 이식술 - 민영주; Young Joo Min; 서철원; Cheol Won Suh; 이제환; Je Hwan Lee; 채영란; Young Ran Chae; 김신; Shin Kim; 배창황; Chang Whang Bae; et al. (The Korean journal of medicine, 1997)
Objectives: Recently high dose chemotherapy with autologous peripheral blood stem cell transplantation (APBSCT) has been investigated with the hope of maximizing tumor response and increasing survival. The purpose of this study is to evaluate the effect, feasibility, and toxicity of high-dose cyclophosphamide, thiotepa, and carboplatin (CTCb) with APBSCT in patients with metastatic or high risk primary breast cancer. Methods: Four cases of high-risk primary breast cancer (with more than 10 involved axillary nodes) and three cases of metastatic disease in complete or partial response were enrolled. Peripheral blood stem cells were mobilized by G-CSF plus chemotherapy, and median number of collected mononuclear cells was 5.44×108/㎏(range, 1.95-7.08×108/㎏). High-dose chemotherapy of cyclophosphamide (1,500㎎/㎡/day), thiotepa (125㎎/㎡/day) and carboplatin (200㎎/㎡/day) was administered for 4 days and peripheral blood stem cells were reinfused to the patients 72 hours after the completion of chemotherapy. Results. The median days of recovery for neutrophil (over 500/㎣) and for platelet (over 50,000/㎣) were 10 (range, 8 to 33) and 30 (range, 10 to 40). One patient suffered from seizure attack and grade 3 hepatotoxicity during high dose chemotherapy, There were no treatment-related death. Four patients with high-risk primary breast cancer remained disease-free at 2, 8, 12 and 19 months post-transplant. In one patient with bone metastasis, complete response was induced following APBSCT. All three patients with metastatic disease remained progression-free at 8, 18 and 19 months post-transplant. Conclusion: High-dose chemotherapy and autologous peripheral blood stem cell transplantation was feasible and would be a potentially effective treatment modality in high risk and metastatic breast cancer.